1998
DOI: 10.1074/jbc.273.1.381
|View full text |Cite
|
Sign up to set email alerts
|

X-gene Product of Hepatitis B Virus Induces Apoptosis in Liver Cells

Abstract: Hepatitis B virus is a causative agent of hepatocellular carcinoma, and in the course of tumorigenesis, the X-gene product (HBx) is known to play important roles. Here, we investigated the transforming potential of HBx by conventional focus formation assay in NIH3T3 cells. Cells were cotransfected with the HBx expression plasmid along with other oncogenes including Ha-ras, v-src, v-myc, v-fos, and E1a. Unexpectedly, the introduction of HBx completely abrogated the focus-forming ability of all five tested oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
156
3
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 43 publications
18
156
3
2
Order By: Relevance
“…Apoptotic cell death of host cells is considered as one of the primary anti-viral defense mechanisms, and many animal viruses are known to encode one or more proteins that interact with apoptotic regulatory pathways. In fact, several lines of evidence suggest that the HBx protein triggers apoptotic cell death in HBV infected hepatocytes (41)(42)(43). However, the experimental models we employed did not show significant apoptotic changes upon expression of either HBx or Nur77 (data not shown), supports the former possibility.…”
Section: Discussionsupporting
confidence: 66%
“…Apoptotic cell death of host cells is considered as one of the primary anti-viral defense mechanisms, and many animal viruses are known to encode one or more proteins that interact with apoptotic regulatory pathways. In fact, several lines of evidence suggest that the HBx protein triggers apoptotic cell death in HBV infected hepatocytes (41)(42)(43). However, the experimental models we employed did not show significant apoptotic changes upon expression of either HBx or Nur77 (data not shown), supports the former possibility.…”
Section: Discussionsupporting
confidence: 66%
“…Evidence that HBx expression is detrimental to cell viability was provided in earlier studies by the di culty in generating stable cell clones that express the X protein (Kim et al, 1998;Oguey et al, 1996). We succeeded in establishing permanent cell lines which stably expressed HBx by isolating hepatocytes from HBx/p53-null and HBx/AT-cyto-MET bitransgenic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained using the lacZ reporter gene (right) are expressed as in (B) (Bergametti et al, 1999;Chirillo et al, 1997;Kim et al, 1998;Su and Schneider, 1997) although both the underlying mechanism and the biological signi®cance of these e ects are still elusive. Moreover, in several studies, HBx overexpression has been shown to directly trigger apoptosis, resulting in strong suppression of colony formation (Chirillo et al, 1997;Kim et al, 1998). In agreement with the latter observations, transfection into CCL-13 cells of an episomic vector (pDR2) carrying the wt WHx gene, reduced e ciency of hygromycin-resistant colony formation, in a dosedependent way ( Figure 4A).…”
Section: X-uvddb Interaction Is Involved In X-mediated Apoptosismentioning
confidence: 99%
“…In others, X appears to act far more upstream, by modulating the signal transduction cascade in the cytoplasm (Benn et al, 1996;Chirillo et al, 1996;Henkler et al, 1998;Kekule et al, 1993;Klein and Schneider, 1997;Lee and Yun, 1998;Su and Schneider, 1996). In addition to its widely documented transactivation activity, X has been reported to interfere with DNA repair (Becker et al, 1998;Wang et al, 1994), cell cycle control (Benn and Schneider, 1995) and apoptosis (Bergametti et al, 1999;Chirillo et al, 1997;Kim et al, 1998;Su et al, 1998). However, the functional connections between these activities and the cellular Xbinding proteins are still missing.…”
Section: Introductionmentioning
confidence: 99%